Toward muzaki: Reconstructing a digital-ready productive zakat ecosystem through an integrated four-pillar model - Abdul Chamid; Ida Nurlaeli; Emiola Habeeb Olasunkanmi; Habeebullah Abdus-salaam (Indonesian Journal of Islamic Economics Research, 2026)
Productive zakat management in Indonesia is constrained by a persistent gap between its estimated potential (IDR 327 trillion) and low realization (13.6%), compounded by the absence of impact-based evaluation and limited integration with digital ecosystems. Prior studies remain fragmented focusing mainly on economic outcomes while lacking an integrated transformation model and overlooking the munfiq stage as a critical transition phase. This study addresses these gaps by reconstructing a digital-ready productive zakat ecosystem aimed at accelerating mustahik-to-muzaki transformation. Using a constructivist qualitative approach with a single case study at BAZNAS Banyumas Regency, data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using the Miles–Huberman–Saldaña interactive model. Findings reveal a pronounced execution gap, particularly in implementation and evaluation, resulting in partial achievement: beneficiaries consistently reach the munfiq stage but fail to transition into verified muzaki. This reflects systemic weaknesses in sustained mentoring, outcome-based evaluation, and integrated data tracking. This study advances the literature by proposing the Integrated Four-Pillar Transformation Model spiritual-ethical, managerial-strategic, economic-business, and social-mentoring and by positioning the munfiq stage as a decisive inflection point in the transformation pathway. Policy implications emphasize the urgency of adopting outcome-based evaluation systems, institutionalizing structured mentoring, and developing digitally integrated zakat ecosystems enabling data-driven monitoring, scalable empowerment, and real-time impact measurement.